Lecturers’ checklist instrument to monitor students’ understanding in distance learning - Sari Muthia Silalahi; Dedy Anwar; Juli Yanti Damanik (Journal of Education and Learning (EduLearn), 2022)
This paper aimed at exploring the results of participant self monitoring using a checklist instrument in distance learning with flipped classroom setting. The participants were 11 lecturers of Bioprocess Engineering Study Program at Institut Teknologi Del (IT Del), Indonesia. The objective of the checklist instrument was for the lecturers to monitor their students’ understanding about the lessons given each week. The data generated from the instrument was analysed descriptively. The results found that pre-class, in-class and out-class are important parts of learning in flipped classroom setting. The data showed that 56% of students achieved good understading of the knowledge taught by their lecturers. The same idea as in-class, attendance checking and interaction between students and lecturers had a key factor in the learning process. It was found that students’ understanding increased by 20% (very good), 62% (good) and 18% (moderate) through questions and answers, discussions, and tests at the end of class. Those were the modes of interactions that had been done in class. In line with an out-class checklist, giving assignments and feedback could improve students understanding into the level of very good (61%), good (27%) and sufficient (10%). with using a checklist tool, participants in this study self-monitored their progress in a flipped classroom while taking distance learning courses online to improve the quality of their class.